Paul Otlet and the Ultimate Prospect of Documentation - Olivier Le Deuff; Arthur Perret (Proceedings from the Document Academy, 2019)
Paul Otlet (1868-1944) has left information science a vast written legacy. He imagined future developments of documentation around new devices. His anticipations have attracted some misunderstandings and criticism. Otlet’s more daring projections were considered utopian but they are best studied in the historical context of his time. We present the relationship between the concepts of documentation and hyperdocumentation, the ultimate prospect of documentation, and the proximity between Otlet’s work and current conceptions of transhumanism in view of his Mundaneum project.